2015
DOI: 10.3390/cancers7010266
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 3: A Help or a Hindrance in Cancer Progression?

Abstract: Desmoglein 3 is one of seven desmosomal cadherins that mediate cell-cell adhesion in desmosomes. Desmosomes are the intercellular junctional complexes that anchor the intermediate filaments of adjacent cells and confer strong cell adhesion thus are essential in the maintenance of tissue architecture and structural integrity. Like adherens junctions, desmosomes function as tumour suppressors and are down regulated in the process of epithelial-mesenchymal transition and in tumour cell invasion and metastasis. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 177 publications
(240 reference statements)
3
41
0
Order By: Relevance
“…Cadherin subtypes are expressed at the highest levels in The number of cadherins as well as distinct features of their gene structure permits precise temporal and spatial transcriptional regulation of cadherin subtypes, and variations in protein structure, particularly the cytoplasmic domain, facilitate interactions that result in both specific modulation of cadherin activity and initiation of intracellular signalling cascades in response to adhesion. The extensive transcriptional and post-transcriptional regulation of cadherins suggests that the level of cadherin cell surface expression and the maintenance of linkage to intracellular binding partners modify cadherin activity [7,8].…”
Section: Role Of Cadherins During Embryogenesis and Developmentmentioning
confidence: 99%
“…Cadherin subtypes are expressed at the highest levels in The number of cadherins as well as distinct features of their gene structure permits precise temporal and spatial transcriptional regulation of cadherin subtypes, and variations in protein structure, particularly the cytoplasmic domain, facilitate interactions that result in both specific modulation of cadherin activity and initiation of intracellular signalling cascades in response to adhesion. The extensive transcriptional and post-transcriptional regulation of cadherins suggests that the level of cadherin cell surface expression and the maintenance of linkage to intracellular binding partners modify cadherin activity [7,8].…”
Section: Role Of Cadherins During Embryogenesis and Developmentmentioning
confidence: 99%
“…The importance of Dsg3 in cell-cell adhesion is highlighted by numerous studies based on pemphigus autoantibodies that demonstrate convincingly that disruption of Dsg3 is a causative factor for the skin and oral lesions [1,48]. However, the action of Dsg3 is not restricted to DSM adhesion and in fact, Dsg3 is present at the plasma membrane beyond the DSMs [1,6,43,54,55]. In vitro studies have shown that extra-junctional Dsg3 "cross-talks" with E-cadherin and regulates various signaling pathways, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Desmoglein-3 (Dsg3), a member of the cadherin superfamily, serves as an adhesion protein in desmosomes and is crucial in the maintenance of epithelia integrity. A growing body of evidence suggests that Dsg3 does not function solely in desmosome adhesion but also acts as a regulator for various signalling pathways that govern cell adhesion, proliferation, differentiation, morphogenesis, as well as cell migration (Brown and Wan, 2015;Chen et al, 2013;Mannan et al, 2011;Rotzer et al, 2016;Tsang et al, 2010;Tsang et al, 2012a;Tsang et al, 2012b). However, the non-junctional functions of Dsg3 remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, the pathogenesis of PV remains not fully understood and constitutes an issue of debate Spindler et al, 2018). In cancer, Dsg3 is found to be upregulated, in particular in squamous cell carcinoma (Chen et al, 2007;Fang et al, 2014;Ferris et al, 2005;Fukuoka et al, 2007;Huang et al, 2010;Liu et al, 2007;Savci-Heijink et al, 2009); though its actual role in tumour progression and metastasis remains to be elucidated (Brown and Wan, 2015).…”
Section: Introductionmentioning
confidence: 99%